Strangeness neutrality and baryon-strangeness correlations - Fu, Wei-jie; Pawlowski, Jan M.; Rennecke, Fabian (Arxiv, 2018)
We derive a simple relation between strangeness neutrality and baryon-strangeness correlations. In heavy-ion collisions, the former is a consequence of quark number conservation of the strong interactions while the latter are sensitive probes of the character of QCD matter. This relation allows us to directly extract baryon-strangeness correlations from the strangeness chemical potential at strangeness neutrality. The explicit calculations are performed within a low energy theory of QCD with 2+1 dynamical quark flavors at finite temperature and density. Non-perturbative quark and hadron fluctuations are taken into account within the functional renormalization group. The results show the pronounced sensitivity of baryon-strangeness correlations on the QCD phase transition and the crucial role that strangeness neutrality plays for this observable.